New Perspectives on Antimicrobial Agents: Long-Acting Lipoglycopeptides - Truc T. Tran; Sara Gomez Villegas; Samuel L. Aitken; Susan M. Butler-Wu; Alex Soriano; Brian J. Werth; MUNITA SEPULVEDA, JOSE MANUEL (My University, 2022)
The long-acting lipoglycopeptides (LGPs) dalbavancin and oritavancin are semisynthetic antimicrobials with broad and potent activity against Gram-positive bacterial pathogens. While they are approved by the Food and Drug Administration for acute bacterial skin and soft tissue infections, their pharmacological properties suggest a potential role of these agents for the treatment of deep-seated and severe infections, such as bloodstream and bone and joint infections.
Keywords: resistant staphylococcus-aureus; in-vitro activity; gram-positive infections; cystic-fibrosis patient; real-world experience; acute bacterial skin; enterococcus-faecium; pharmacodynamic evaluation; intracellular activity; dalbavancin therapy; anti-bacterial agents; anti-infective agents; glycopeptides; gram-positive bacterial infections; humans; lipoglycopeptides; teicoplanin; dalbavancin; daptomycin; linezolid; lipoglycopeptide; oritavancin; rifampicin; teicoplanin; vancomycin; antiinfective agent; glycopeptide; teicoplanin; antibiotic sensitivity; antibiotic therapy; article; bacteremia; bacterial growth; bactericidal activity; bone and joint infections; broth dilution; clinical outcome; drug mechanism; enterococcus faecalis; enterococcus faecium; gene cluster; gram positive cocci; human; in vitro study; minimum inhibitory concentration; nonhuman; treatment duration; vancomycin resistance; vancomycin resistant enterococcus; chemistry; gram positive infection